KEKUATAN HUKUM SURAT KETERANGAN PENGUASAAN TANAH (SKPT) SEBAGAI BUKTI HUKUM PENGUASAAN ATAS SEBIDANG TANAH (STUDI DI KOTA PONTIANAK) - DONO DOTO WASONO, S.H. NPM.A2021141034, JURNAL MAHASISWA S2 HUKUM UNTAN (Jurnal NESTOR Magister Hukum, 2017)
ABSTRACT This thesis discusses the Legal Strength of Land Tenure Certificate (SKPT) as a Proof of Legal Mastery over a Plot of Land (Study In Pontianak City). From the results of this thesis research obtained the conclusion that the Land Tenure (SPT) has the force of law as evidence of the mastery of a plot of land. a land certificate in Pontianak City, where people in the city of Pontianak much entrust the process of buying land to the head of the village chief. The village head is a key figure in urban governance and is an influential formal leader in community life. Service to the making of certificate of land ownership has been regulated in Mayor Pontianak Regulation No. 28 of 2016 on Amendment of Mayor Regulation No. 51 Year 2015 About Service Standard Of Sub District And Village In The Environment Of Pontianak Municipal Government. Land tenure (SPT) which is the base of rights that are widely used in various regions, in the country there are different terms but this is the same as the letter of letter or some people call it